AMERICAN CRUISE MISSILES - Ward, W. (Scientia Militaria - South African Journal of Military Studies, 2012)
Mankind’s strivlng to establish a superior potential for extermination of antagonistic fellow beings, as a deterrent to those whom he feels threaten his way of life or even existence, has motivated the development of successive generations of ’super weapons’ and counter weapons. Thus it is that we now hear the acclaimation for what supposes to be the newest brainchild of this human fear and insecurity, the American cruise missiles. Much has been written about this new American ’wonder weapon’ and its capabilities which will argueably give America an advantage over the Soviet Union in the event of an ’ultimate conflict’.